CSPα in neurodegenerative diseases - Huang, Liqin; Zhang, Zhaohui (Frontiers in Aging Neuroscience, 2022)
Adult-onset neuronal ceroid lipofuscinosis (ANCL) is a rare neurodegenerative disease characterized by epilepsy, cognitive degeneration and motor disorders, which is caused by mutations in the DNAJC5 gene. In addition to being associated with ANCL disease, the cysteine string proteins α (CSPα) encoded by DNAJC5 gene has been implicated in several neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease. However, the pathogenic mechanism responsible for these neurodegenerative diseases have not yet been elucidated. This article reviews the functional properties of CSPα protein itself and the related mechanisms of neurodegenerative diseases.